Perlindungan Hukum terhadap Driver Maxim Akibat Pemesanan Orderan Fiktif/Penipuan Food and Goods and Delivery dengan Pembayaran COD pada Minimarket Kepada Costumer di Wilayah Kota Kupang - Beda Soedrio; Rudepel Petrus Leo; Deddy R. Ch. Manafe (Pusat Riset dan Inovasi Nasional, 2024)
This research discusses the legal protection of maxim drivers due to fictitious order booking/fraud food and goods and delivery with cod payment at minimarkets to customers in the Kupang City Area. Through an empirical juristic approach, primary data is obtained through interviews, observations, and documentation studies. The results showed that the form of company action to help Driver partners affected by Fictitious orders after account blocking carried out by the Company by restoring the Driver's account The Maxim online motorcycle taxi recovered the Driver's account who reported the fictitious order to the Operations Office no later than 1 month after the auto suspension was obtained and it was proven that the Driver did not make the mistake. Maxim online ojek drivers who have reported themselves and fulfilled the submission requirements in the form of returning the reting scor on Maxim driver accounts that get a decrease in reting. Legal efforts made in tackling cases of fraud or fictitious orders by providing pre-emtif and preventive actions.